Low Level of Advanced Glycation End Products in Serum of Patients with Allergic Rhinitis and Chronic Epstein-Barr Virus Infection at Different Stages of Virus Persistence - Svitlana Zubchenko; Iryna Kril; Halyna Potemkina; Anna Havrylyuk; Aleksandra Kuzan; Andrzej Gamian; Valentyna V. Chopyak (Journal of Immunology Research, 2022)
Advanced glycation end products (AGEs) are formed in a nonenzymatic reaction of the reducing sugars with amino groups of proteins, lipids, and nucleic acids of different tissues and body fluids. A relatively small number of studies have been conducted on the role of AGEs in allergic inflammation. In this study, patients with allergic rhinitis (AR) were examined for the presence of Epstein-Barr virus and the content of fluorescent and nonfluorescent AGEs. We have also determined the level of a unique epitope (AGE10) which was recently identified in human serum using monoclonal antibodies against synthetic melibiose-derived AGE (MAGE). The levels of AGE10 determined with an immunoenzymatic method revealed no significant difference in the patients’ blood with intermittent AR and chronic EBV persistence in the active and latent phases. It has been shown that there is a statistically significantly smaller amount of AGEs and pentosidine in groups of patients, both with and without viremia, than in healthy subjects. In turn, higher levels of immune complexes than of AGE10 were detected in the groups of patients, in contrast to the control group, which had lower levels of complexes than AGE10 concentration. In patients with active infection, there is even more complexes than of noncomplexed AGE10 antigen. The lower level of AGE in allergic rhinitis patient sera may also be due, besides complexes, to allergic inflammation continuously activating the cells, which effectively remove glycation products from the body.